(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Justified by the environmental hazards and eco-system disruption in Nigeria, this dissertation investigated the relationship between corporate social responsibility and financial performance of quoted oil and gas companies in Nigeria. The research adopted the ex post facto research design and data was collected from a sample of nine (9) listed oil and gas companies for a period of eleven (11) years from 2010 to 2020. The corporate social responsibility activities of the oil and gas companies in Nigeria were measured against financial performance. The panel least square (PLS) regression estimation technique was used for data analysis. Other statistical/econometric estimation techniques used in the research included: Pearson correlation, Augmented Dick-Fuller (ADF) unit root test, Breusch-Pagan-Godfrey heteroskedasticity and the Hausman test. Findings of the research revealed: a non-significant negative relationship between employees’ training activities and return on assets; employees’ training activities and return on equity had a negative and significant relationship ;there was a non-significant negative relationship between environmental compliance activities and return on assets; a significant positive relationship between environmental compliance activities and return on equity; a non-significant positive relationship between community development activities and return on assets; a non-significant negative relationship between community development activities and the return on equity. The research thus concluded that costs associated with employees training and environmental compliance activities contribute meaningfully to return equity however, none of the variable are significantly enhance return on assets. Based on the conclusions, it is recommended that: Oil and gas companies conduct a thorough review/audit of their employees’ training programs enhance its contribution to financial performance. It is further suggested that oil and gas companies invest more in environmental compliance activities that has the potential to reduce resources expended in environmental remediation programs; community development activities be designed to foster peaceful coexistence between the company and local communities in which the oil and gas companies operate.